2007
DOI: 10.4489/myco.2007.35.4.196
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activities and Substrate Degradation by Fungal Isolates on Cassava Waste During Solid State Fermentation

Abstract: The growth and bioconversion potential of selected strains growing on cassava waste substrate during solid state fermentation were assessed. Rhizopus stolonifer showed the highest and the fastest utilization of starch and cellulose in the cassava waste substrate. It showed 70% starch utilization and 81% cellulose utilization within eight days. The release of reducing sugars indicating the substrate saccharification or degradation potential of the organisms reached the highest value of 406.5 mg/g by R. stolonif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The highest CMCase (14.86 IU/ml) and FPase (14.66 U/ml) activity was achieved at 1%. Our studies are comparable to Abd-Elrsoul and Bakhiet (2018) who also reported sodium nitrate as a best nitrogen source, but contrary to Pothiraj and Eyini (2007) who reported that optimal cellulase production can be achieved from organic nitrogen sources, such as a yeast extract and peptone. Process optimization for enhanced production of cellulases form locally isolated fungal strain by submerged fermentation…”
Section: Resultssupporting
confidence: 84%
“…The highest CMCase (14.86 IU/ml) and FPase (14.66 U/ml) activity was achieved at 1%. Our studies are comparable to Abd-Elrsoul and Bakhiet (2018) who also reported sodium nitrate as a best nitrogen source, but contrary to Pothiraj and Eyini (2007) who reported that optimal cellulase production can be achieved from organic nitrogen sources, such as a yeast extract and peptone. Process optimization for enhanced production of cellulases form locally isolated fungal strain by submerged fermentation…”
Section: Resultssupporting
confidence: 84%
“…The cellulose degradation is mostly facilitated by the synergistic action of hydrolytic enzymes (cellulases) secreted by the filamentous fungus during the fermentation (Chesson, 1993;Datta and Chakravarty, 2001). Pothiraj and Eyini (2007) also observed that R. stolonifer showed the highest and fastest utilization of cellulose in the solid state fermentation of cassava waste which resulted in 51.24% utilization of cellulose on the 2nd day.…”
Section: Amino Acidmentioning
confidence: 73%
“…Therefore, although it has not been detected in this study, it will be of great interest to analyze the enzyme activities of A. corymbifera on sterile culture and different culture conditions. Although several studies have shown a broad spectrum of enzymatic activity from R. stolonifer , including starch utilization [ 16 ], our assay did not successfully detect amylase activity, possibly because of differences in the assay conditions or culture conditions.…”
mentioning
confidence: 79%